PROBLEMS AND PROSPECTS OF LOCAL SELF-GOVERNMENT IN THE FEDERAL CITIES: MOSCOW AND ST. PETERSBURG - E. Hmelchenko (Вестник университета, 2017)
The basic approaches to the construction of an effective system of local government in cities of federal significance - Moscow and St. Petersburg. Analyzes the key problems of development of local self-government, the basic directions to improve the legal, territorial, economic basics of local self-government.